Cross-Cultural Adaptation and Psychometric Properties of an Arabic Version of the Western Ontario Shoulder Instability Index (WOSI) - Khaja, Dr Aliaa; Bouhamra, Dr Ahmed; Hanna, Dr Sager; Maqdis, Dr Ali (International Journal of Innovative Research in Medical Science, 2020)
Background: The Western Ontario Shoulder Instability Index (WOSI) score is a tool that helps with self-assessment of the shoulder’s functional status in patients experiencing instability problems.The purpose of this study was the cross-cultural adaptation of WOSI into Arabic and assessment of its psychometric properties in comparison to a gold standard-questionnaire, namely the Arabic Disability of the Arm, Shoulder and Hand (DASH) score. Material & Methods: 100 patients participated in this survey, tested initially and retest after two months. The internal consistency tests were performed using Cronbach's alpha. Besides, Pearson's Correlation and Standard response mean (SRM) were calculated to estimate criterion validity and responsiveness of the Arabic WOSI in comparison to the Arabic DASH. Results: The Arabic WOSI had a Cronbach's alpha score of 0.85 at the baseline and 0.91 at the follow-up time period. All subscales had an internal consistency greater than 0.7, except Sport/Work (0.69 at follow-up). A strong correlation with Arabic DASH score was observed (r = 0.79 at baseline & 0.87 at Follow-up) which suggested good validity. Also, moderately correlated changes of baseline to follow-up in DASH and WOSI indicated moderate responsiveness. No ceiling and floor effects were observed among the responses. Conclusion: Overall, the Arabic version of WOSI proved to be a good and reliable diagnostic tool for patients with shoulder instability.